(untitled) (Journal of Computational Mathematics, 1998)
In this paper, the superconvergence of a class of Wilson-like elements is considered. A superconvergent estimate on the centers of elements and some superconvergence recoveries on the four vertices and the four midpoints of edges of elements are also obtained for piecewise strongly regular quadrilateral subdivisions.